2018
DOI: 10.1088/2057-1976/aabef1
|View full text |Cite
|
Sign up to set email alerts
|

In vitrosingle-unit recordings reveal increased peripheral nerve conduction velocity by focused pulsed ultrasound

Abstract: Abstract. Ultrasound that is widely used in medical diagnosis has drawn growing interests as a noninvasive means of neuromodulation. Focused pulsed ultrasound (FPUS) effectively modulates neural encoding and transmission in the peripheral nervous system (PNS) with unclear mechanism of action, which is further confounded by contradictory experimental outcomes from recordings of compound action potentials (CAP). To address that, we developed a novel in vitro set up to achieve simultaneous single-unit recordings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 50 publications
2
34
0
Order By: Relevance
“…We, along with some other research groups, have demonstrated that US stimulation on the PNS, with I SPTA between 1 and 200 W/cm 2 , is unlikely to induce a sufficient temperature change in the target region to elicit temperature-driven neuromodulation [43,47]. This intermediate intensity range has been explored on the PNS by several neuromodulation studies, which have been systematically reviewed in the subsequent sections.…”
Section: Intensitymentioning
confidence: 97%
See 3 more Smart Citations
“…We, along with some other research groups, have demonstrated that US stimulation on the PNS, with I SPTA between 1 and 200 W/cm 2 , is unlikely to induce a sufficient temperature change in the target region to elicit temperature-driven neuromodulation [43,47]. This intermediate intensity range has been explored on the PNS by several neuromodulation studies, which have been systematically reviewed in the subsequent sections.…”
Section: Intensitymentioning
confidence: 97%
“…Several studies have reported neuromodulatory effects on the CNS, with US intensity <1 W/cm 2 [15,[20][21][22]28]. So far, there seem to be no studies reporting appreciable neuromodulatory effects on the PNS with US intensity <1 W/cm 2 [43]. On the other hand, I SPTA over 200 W/cm 2 is generally considered as high-intensity US and has been tested in a number of clinical trials [44,45], after being approved by the FDA, for the ablation of cancer cells in patients via local elevation of temperature up to 85 • C [44,46].…”
Section: Intensitymentioning
confidence: 99%
See 2 more Smart Citations
“…All procedures were approved by the University of Connecticut Institutional Animal Care and Use Committee. Sciatic nerves of male C57BL/6 mice (6-8 weeks, Taconic, Germantown, NJ, United States) were harvested for extracellular recordings from teased nerve filaments as detailed previously (Chen et al, 2017;Ilham et al, 2018). Mice were anesthetized by isoflurane inhalation, euthanized by exsanguination from perforating the right atrium, and perfused through the left ventricle with oxygenated Krebs solution (in mM: 117.9 NaCl, 4.7 KCl, 25 NaHCO 3 , 1.3 NaH 2 PO 4 , 1.2 MgSO 4 , 2.5 CaCl 2 , and 11.1 D-glucose).…”
Section: Surgical Proceduresmentioning
confidence: 99%